A focus on adolescent mental health and wellbeing in Europe, central Asia and Canada. Health Behaviour in School-aged Children international report from the 2021/2022 survey. Volume 1. - Cosma, Alina; Abdrakhmanova, Shynar; Taut, Diana; Schrijvers, Karen; Catunda, Carolina; Schnohr, Christina (World Health Organization. Regional Office for Europe, 2023)
vii, 56 p.